How does e-commerce live streaming in China affect consumers’ purchasing intentions? - Miao, Yihe (2024)
In recent years, the live streaming sector has had significant growth due to the concurrent rise of the national high-tech industry and rapid economic development. This industry has effectively impacted the lifestyle and buying habits of contemporary individuals by capitalizing on its distinctive developmental advantages. When comparing live streaming services combined with e-commerce to traditional e-commerce, it becomes evident that the former offers certain advantages stemming from the incorporation of social media features. These characteristics serve to foster customer engagement and participation in live purchasing experiences. The primary aim of this research is to predict the impact of e-commerce live streaming features on the perceived trust of Chinese consumers, and therefore, on their purchase intention. Thus, employing literature review, questionnaire survey, and statistical analysis, this study categorizes the attributes of e-commerce live broadcasting into four distinct dimensions: primary broadcast influence, product display, price promotion, and customer assessment. The data analysis was conducted using SPSS26, and the SOR model was employed to investigate the impact of e-commerce live broadcasting characteristics on customers' buy intention through the perception of trust. The findings indicate that many factors, such as anchoring, product display, price promotion, and customer evaluation, have a notable beneficial impact on customers' perceived trust in e-commerce live streaming. Furthermore, it is shown that perceived trust has a favorable impact on consumers' desire to make purchases. This paper presents practical recommendations for e-commerce enterprises, drawing on the findings of the research. The aim is to enable these enterprises to leverage the unique features of e-commerce live broadcasting in order to enhance customers' purchase intention, establish a favorable reputation, and increase their visibility. To optimize user engagement and retention, it is crucial to establish meaningful and profound interactions with consumers.